(untitled) (Journal of Economic Research & Business Administration, 2015)
This article examines trends in the development of investment activities and priorities of state investment policy in Kazakhstan. The investment policy is the most important element of economic strategy of the country, and is defined by its purposes and tasks. The investment policy has to assist as much as possible to development of the market relations in the country, production restructuring, and also it is essential to increase investment activity both state, and private domestic and foreign investors. Formation of the purposeful state investment policy focused on the solution of macroeconomic problems of the state, on intensive structural and technological transformations has to provide strengthening of a regulating and coordinating role of the state in attraction and use of investments. Transition to the market relations, creation of economy of open type demand changes of functions of the state in the investment sphere. Further encourage foreign direct investment in the economy will enable the successful development of infrastructure, human resource disclosure (human) capacity, strong media coverage of investment opportunities in various sectors.